Generation mean analysis to estimate genetic parameters for desirable horticultural traits in garden pea (Pisum sativum) - SHARMA, AKHILESH; KAPUR, POOJA; KATOCH, VIVEKA (The Indian Journal of Agricultural Sciences, 2012)
Generation means analysis was carried out to estimate the nature and magnitude of gene action in order to formulate breeding strategy for identifying the segregants with desirable horticultural traits and resistance to powdery mildew disease. Two commercially grown powdery mildew susceptible varieties Azad P-I and Green Pearl and three resistant lines DPP 9411, DPP 9418-06 and Sugar Giant were used to develop three crosses, viz. Green Pearl × Sugar Giant, DPP 9411 × DPP 9418-06, and Azad P-I × Sugar Giant to achieve the objectives. The presence of epistatic interaction for majority of the traits in all three crosses was observed as reflected by the significance of simple additive-dominance model. The results revealed that the nature and magnitude of gene effects differed in different crosses and showed the importance of additive as well as non-additive gene effects in the inheritance of different characters with preponderance of the latter. In view of the parallel role of additive and non-additive gene effects, selection in the segregating generations should be delayed to later generations to diminish the dominance gene effects. Duplicate type of epistasis was also found for some of the traits in certain cross combinations whose effect can be eliminated by following sophisticated selection procedure such as reciprocal recurrent selection and/or biparental mating in early segregating generations for the development of high- yielding garden pea varieties with desirable horticultural traits.